IPC-based Dynamic SM management on GPGPU for Executing AES Algorithm - Son, Dong Oh; Choi, Hong Jun; Kim, Cheol Hong (韓國컴퓨터情報學會論文誌, 2020)
Modern GPU can execute general purpose computation on the graphic processing unit, and provide high performance by exploiting many core on GPU. To run AES algorithm efficiently, parallel computational resources are required. However, computational resource of CPU architecture are not enough to cryptographic algorithm such as AES whereas GPU architecture has mass parallel computation resources. Therefore, this paper reduce the time to execute AES by employing parallel computational resource on GPGPU. Unfortunately, AES cannot utilize computational resource on GPGPU since it isn't suitable to GPGPU architecture. In this paper, IPC based dynamic SM management technique are proposed to efficiently execute AES on GPGPU. IPC based dynamic SM management can increase and decrease the number of active SMs by using IPC in run-time. According to simulation results, proposed technique improve the performance by increasing resource utilization compared to baseline GPGPU architecture. The results show that AES improve the performance by 41.2% on average. 최신 GPU는 GPGPU를 활용하여 범용 연산이 가능하다. 뿐만 아니라, GPU는 내장된 다수의 코어를 활용하여 강력한 연산 처리량을 제공한다. AES 알고리즘은 다수의 병렬 연산을 요구하지만 CPU 구조에서는 효율적인 병렬처리가 이뤄지지 않는다. 따라서, 본 논문에서는 강력한 병력 연산 자원을 활용하는 GPGPU 구조에서 AES 알고리즘을 수행함으로써 AES 알고리즘 처리시간을 줄여보았다. 하지만, GPGPU 구조는 AES 알고리즘 같은 암호알고리즘에 최적화되어 있지 않다. 그러므로 AES 알고리즘에 최적화될 수 있도록 재구성 가능한 GPGPU 구조를 제안하고자 한다. 제안된 기법은 SM의 개수를 동적으로 할당하는 IPC 기반 SM 동적 관리 기법이다. IPC 기반 SM 동적 관리 기법은 GPGPU 구조에서 동작하는 AES의 IPC를 실시간으로 반영하여 최적의 SM의 개수를 동적으로 할당한다. 실험 결과에 따르면 제안된 동적 SM 관리 기법은 기존의 GPGPU 구조와 비교하여 하드웨어 자원을 효과적으로 활용하여 성능을 크게 향상시켰다. 일반적인 GPGP 구조와 비교하여, 제안된 기법의 AES의 암호화/복호화는 평균 41.2%의 성능 향상을 보여준다.